Ouvir a Arquitectura. O espaço como último instrumento sonoro - Andreia Catarina Rocha de Almeida (2009)
The purpose of this work is to show the hypotheses of inverting the current or popular consideration of acoustic architecture, which favors the elimination of the negative factors of the sound (almost exclusively treated as noise), through an alternative proposal of the understanding of the sonic space and a positive attitude of the recovery of sound quality in architecture. It focus on the fundamental aspects related to Sound and Space from concepts to terminologies, associating theoretical framework to practical field of the materialization of those concepts. It is our objective to study spaces and shapes that generate many sound events that extend music to silence. Sound is a powerful matter, responsible for the changing, definition and quality of space. Its manipulation triggers positive or negative stimuli in humans. So according to his/her sensory experience, the individual selects the information as s/he processes the space appropriation. In that sense it is important to create acoustic balanced environments, with the allocation of character or sound effect that provides comfort and life quality. Spaces with different shapes and materials, produce many sounds or sound effects, timbre and tone. Reciprocally, some musical works are exclusively compound for a specific spaciousness, which generates effects in the music, through its physical properties. Naturally in the Industrial and Electric Revolution, many ways of musical expression emerged, influenced by the new life's rhythms and sounds. Nowadays the sonorous dimension has exagerate proportions, that greatly exceed the body, ear and voice limits. To face this problem the attitude has been to isolate and absorb the sound, and acoustic as been considered as a pathological factor in the project. However the individual necessity of being connected with the world, gives more responsibility to the architect as far as the conception of the caps and spaces that establish such a connection are concerned. It becomes urgent the search of a common vocabulary both to acoustic and architecture, taking the sound as a link and a creativity argument.